A ladder to the sky : a novel - Boyne, John, 1971- (Hogarth, 2018)
Aspiring writer Maurice Swift, whose desire for fame exceeds his talent, uses a chance meeting with celebrated novelist Erich Ackermann in a West Berlin hotel in 1988 to obtain secrets about Ackermann's wartime activities, which becomes material for his first novel.